Compreensibilidade e disseminação da informação contábil: um enfoque na teoria semiótica - Silva, Carlos Eduardo Gomes da (2012)
Several studies show that one of the major problems in understanding the accounting information relies on its terminology. Accordingly, this study aimed to understand how the communication process between journalists and companies Investors Relations areas is, in order to verify where the problems to understand accounting information are, considering that accounting information has a closed structure and its own taxonomy. The choice of journalists was due to the fact that they act as translators of accounting information received to the general public, while the Investors Relations area is seen as the spokesman for the company s shareholders, both considered, then, as a secondary source of accounting information. The survey covered as sample two hundred journalists and 155 companies that have shares listed on BM&F BOVESPA. Data were collected through a questionnaire containing open and closed questions, made available on the web and treated by techniques of content analysis and factor analysis. In general, the analysis of the results enabled to verify that journalists use the same sources of accounting information that the other external users, however there is not effective interaction with the Investor Relations areas. Additionally, it was found that accounting needs further simplification in its terminology, because it is seen that their translators cannot perfect fulfill this role.